Mechanical safety of reinforced concrete structures at all stages of the life cycle - Terekhov Ivan A.; Trekin Nikolay N.; Kodysh Emil N.; Shmakov Sergey D. (E3S Web of Conferences, 2023)
Ensuring the mechanical safety of operated buildings at all stages of the life cycle is an urgent task. This is especially important when planning major repairs and reconstruction in buildings, as well as determining the period of safe operation from the moment of the survey, i.e. clarification of the remaining service life. The total service life at the design stage is set by the customer and the general designer in accordance with the recommendations of GOST 27751-2014 «Reliability for constructions and foundations. General principles». Mechanical safety and durability are ensured when calculating structures using the limit state method, assigning protection measures depending on the operating conditions, as well as complying with the requirements of SP 255.1325800.2016 «Buildings and structures. Operating rules. General Provisions». A method for preliminary assessment of the mechanical safety of buildings and their structures is proposed for consideration, which eliminates some of the shortcomings of existing methods for calculating the residual life by physical wear (damage) of building structures based on the results of a visual inspection, the basis of which is the dependence of the allowable safe operation period on the percentage of reduced bearing capacity. It is proposed to use the results of a visual inspection performed in accordance with GOST 31937-2011 «Buildings and constructions. Rules of inspection and monitoring of the technical condition».